Ecological criteria and indicators for tropical forest landscapes: challenges in the search for progress - Sheil, Douglas; Nasi, Robert; Johnson, B. (2004)
In the quest for global standards, “Criteria and Indicators” (C&I) are among the foremost mechanisms for defining and promoting sustainable tropical forest management. This paper examines some challenges posed by this approach, focusing on examples that reflect the ecological aspects of tropical forests at a management-unit level and assessments such as those required in timber certification. C&I can foster better forest management. However, there are confusions and tensions to reconcile between general and local applications, between the ideal and the pragmatic, and between the scientific and the democratic. To overcome this requires a sober appraisal of what can realistically be achieved in each location and how this can best be promoted. Good judgment remains the foundation of competent management. Data can inform this judgment, but an over-reliance on data collection and top-down bureaucratic interventions can add to problems rather than solving them. These arguments stress compromise, planning, guided implementation, and threat preparedness. Importance is also placed on skills and institutions: the building blocks of effective forest management. The authors suggest some options for improving forest management. Although a wider discussion of these issues is necessary, procrastination is harmful. Action is needed.